2003
DOI: 10.1002/ptr.1231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antimalarial properties and standardization of tablets of Azadirachta indica (Meliaceae) in mice

Abstract: The antimalarial activities of the tablet suspension of the bark and leaf of Azadirachta indica were evaluated on Plasmodium yoelli nigeriensis infected mice. The tablet suspensions exhibited high prophylactic, mode-rate suppressive and a very minimal curative schizonticidal effect. No animal was cured of the infection in the curative test and there was not much increase in the survival time of the animals compared with the control. The tablet suspensions from the leaf and bark at a concentration of 800 mg/kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 7 publications
(10 reference statements)
0
25
0
Order By: Relevance
“…Among the species displaying an antiplasmodial activity, Azadirachta indica (Meliaceae) (Dhar et al, 1998; El Tahir et al, 1999;Isah et al, 2003), Bixa orellana (Bixaceae) (Deharo et al, 2001), Brucea javanica (Simaroubaceae) (Murnigsih et al, 2005), Eurycoma longifolia (Simaroubaceae) (Chan et al, 2004) have been already reported for their antimalarial activity. Although the samples collected in Cambodia may differ from samples from other locations.…”
Section: Discussionmentioning
confidence: 99%
“…Among the species displaying an antiplasmodial activity, Azadirachta indica (Meliaceae) (Dhar et al, 1998; El Tahir et al, 1999;Isah et al, 2003), Bixa orellana (Bixaceae) (Deharo et al, 2001), Brucea javanica (Simaroubaceae) (Murnigsih et al, 2005), Eurycoma longifolia (Simaroubaceae) (Chan et al, 2004) have been already reported for their antimalarial activity. Although the samples collected in Cambodia may differ from samples from other locations.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve Nigerian medicinal plants have been reported to exhibit activities in vitro and in vivo include Azadirachta indica MacKinnon et al, 1997;Isah et al, 2003), Morinda lucida , Khaya grandifoliola Bickii et al, 2000), Quassia amara (Ajaiyeoba et al, 1999;Bertani et al, 2005), Guiera senegalensis (Iwalewa et al, 1990;Ancolio et al, 2002), Tithonia diversifolia (Goffin et al, 2002;Elufioye and Agbedahunsi, 2004), Vernonia amygdalina (Masaba, 2000;Abosi and Raseroka, 2003), Cassia occidentalis (Iwalewa et al, 1990;Tona et al, 1999;Zirihi et al, 2005), Crossopteryx febrifuga Elufioye and Agbedahunsi, 2004), Spathodea campanulata (Makinde et al, 1988;Dhanabalan et al, 2008), Momordica balsamina (Benoit-Vical et al, 2006) and Picralima nitida (Okokon et al, 2007a;Iwu and Klayman, 1992). Azadirachta indica antimalarial activity is attributed to a substantial oxidative stress during malaria infection; it affects all stages of maturation of the gametocytes, unlike artemisinin and primaquine that seem to affect only the immature stages (Dhar et al, 1998).…”
Section: Scientific Authentication Of Antimalarial Activities Of Nigementioning
confidence: 99%
“…It is an evergreen, fast growing tree, up to 25 m in height and is used in traditional medical practice in form of an aqueous decoction of the leaves, stem bark and root . Due to the importance of this plant as an antimalarial remedy in Nigeria, efforts were made to produce the tablet suspensions of the bark and leaf which exhibited high prophylactic, moderate suppressive and a very minimal curative schizonticidal effect in mouse model of malaria (Isah et al, 2003). Khaya senegalensis and Khaya grandifoliola are often planted by roadsides for shade.…”
Section: Nigerian Medicinal Plants Used For Malaria Treatmentmentioning
confidence: 99%
“…Notable among these were fruits of Allium cepa L., unripe fruits of A gedunin-rich extract of A. indica was safe and registered in Nigeria as 250mg capsules of IRACARP®; adult treatment cost around US $6.00 (Wells, 2011). However, Isah et al (2003) found that although A. indica tablet suspensions exhibited high prophylactic, mode-rate suppressive and very minimal curative schizonticidal effects, no animal was cured of Plasmodium yoelli nigeriensis infection and there was no significant increase in the survival time of the animals compared with the control. They extrapolated that an adult human needed to ingest a minimum of 48 grams of powdered A. indica per day, an amount that was not practicable.…”
Section: Nigeriamentioning
confidence: 97%